ANALISIS SOSIOLOGI SASTRA TERHADAP LEGENDA BATU TERMANU DI DESA TERMANU KECAMATAN ROTE TENGAH KABUPATEN ROTE NDAO - Irwan Soulisa; Imarnilde E. Fanggi (SOSCIED, 2023)
The author's research objective is to describe the social values contained in the Legend of Batu Termanu. And to describe the public's view of the Legend of Batu Termanu. The research formulation is in the form of . What social values are contained in the Legend of Batu Termanu? What are the public's views on the Legend of Batu Termanu? In this research, the author discusses the Sociological Literary Analysis of the Legend of Batu Termanu in Termanu Village, Rote Tengah District, Rote Ndao Regency. The problem in this research is the literary sociological values contained in the Legend of Batu Termanu and the public's views on the Legend of Batu Termanu. The legend of Batu Termanu is a form of story owned by the people of Termanu, which is precisely located in Termanu Village, Rote Tengah District, Rote Ndao Regency. The method used in analyzing this research problem is a descriptive method with field research techniques. This research uses literary sociology theory. Data in the form of primary data and secondary data and data sources from sources. Data collection techniques are through 1) observation techniques, 2) interview techniques, 3) documentation techniques. The researcher's data analysis techniques use 1) data reduction, 2) data display (data presentation) , 2) Conclusion. Meanwhile, the validity of the author's data uses 1) Credibility Test, 2) Source Triangulation, 3) Theory Trianggulation. The conclusions obtained in researching this legend include: compassion, responsibility, and harmony in life. Based on this research, until now Batu Termanu is still located in Termanu Village, Rote Ndao Regency